Acceptability of a theory of planned behaviour email-based nutrition intervention - Kothe, E.; Mullan, Barbara (Oxford University Press, 2014)
This study investigated feasibility and acceptability of a new email-delivered intervention promoting fruit and vegetable consumption in a university-based population of Australian young adults. The study explored whether there are differences in the reported feasibility and acceptability between demographic groups within the population of interest and at three levels of intervention intensity. The email-delivered intervention program consists of an implementation intention ‘planning task’ and between 3 and 15 short email messages over a 15-day study period. The intervention program was developed using the Theory of Planned Behaviour and was designed to modify perceived behavioural control. One hundred and ten participants (mean age = 19.21 years, 25.6% male) completed the feasibility and acceptability questionnaire at Day 15. This questionnaire contained items about all intervention components. High acceptability and feasibility scores were found for all intervention parts and at all levels of intervention intensity. There were few significant differences in the reported acceptability of items between key demographic sub-groups, and no differences in reported acceptability at different levels of intervention intensity. These results suggest that this email-delivered intervention is an acceptable and feasible tool for promoting fruit and vegetable consumption for participants in the target population.